Immobilization of TiO2 into polyethersulfone matrix as hybrid photocatalyst for effective degradation of methyl orange dye - Mohd Hir, Zul Adlan; Moradihamedani, Pourya; Abdullah, Abdul Halim; Mohamed, Mohamad Azuwa (Elsevier, 2017)
A series of polyethersulfone-TiO2 (PES/TiO2) film photocatalysts were prepared by a phase inversion technique and subsequently used in the photodegradation of methyl orange dye (MO). The photoactivity of the films increased with increasing TiO2 content up to 13 wt% (PT-13). The photodegradation of MO followed pseudo first-order kinetics and complete removal of MO was almost achieved in acidic conditions. The PT-13 film was found to retain its high degradation efficiency even after 5 cycles indicating the stability of the film photocatalyst.